Pondok Pesantren Mahfilud Duror II Jember pada Era Kepemimpinan KH. Ali Wafa, 1992-2019 - Muhammad Ja'far Shodiq; Adetia Andri; Nurul Hasan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to describe the leadership of KH. Ali Wafa at the Mahfilud Duror II Islamic Boarding School since 1992-2019. The method used in this research is a qualitative method with a historical historical approach in a diachronic perspective. The results of this study illustrate that the leadership of KH. Ali Wafa at the Mahfilud Duror II Islamic Boarding School since 1992-2019 is a charismatic-transformative leadership. The progress that has occurred and the authority possessed by the kiai in the field of religion and management of Islamic boarding schools are evidence of KH's success. Ali Wafa became the leader of the Mahfilud Duror II Islamic Boarding School.